EFFECT OF HYDROCOLLOID TYPE AND GINGER EXTRACT ON THE PROPERTIES OF RED BEETROOT JELLY CANDY (Beta Vulgaris L.). - Fitriah, Arsinah Habibah; Gading, Inges Manggar; Tri Dewanti Widyaningsih; Wulan, Siti Narsito; Sujuti, Hidayat (Jurnal Teknologi Pertanian, 2025)
Jelly candy is a type of soft candy made with the addition of hydrocolloids. Currently, jelly candies are widely made with ingredients that can enhance their nutritional and functional value. Red beet, a material rich in bioactive compounds, can be used as a raw material for making jelly candy. Processing red beet into jelly candy may increase its acceptance due to reduced off-flavors. This study aimed to determine the effect of different types of hydrocolloids and the addition of ginger extract on the physicochemical and organoleptic properties of red beet jelly candy. The research method used was a nested design with three replications. The red beet jelly candy was made with different types of hydrocolloid (agar and carrageenan) and different concentrations of ginger extract (0%, 1%, and 2%). The results showed that the difference in the type of hydrocolloid significantly affected the ash content, nitrate and nitrite content, total phenol, and total betalain content of the product. While the addition of ginger extract nested in the type of hydrocolloid had a significant effect on the a* value, antioxidant activity, total phenol, and total betalain content of the product. The best treatment was determined using the Zeleny method. Data processing results showed that the best treatment obtained was agar jelly candy with the addition of 0% ginger extract, with an antioxidant activity value of 530.15 ppm.